Burden of vasomotor symptoms in France, Germany, Italy, Spain, and the United Kingdom - DiBonaventura MD; Chandran A; Hsu MA; Bushmakin A (Dove Medical Press, 2013)
Marco daCosta DiBonaventura,1 Arthi Chandran,2 Ming-Ann Hsu,3 Andrew Bushmakin41Health Outcomes Practice, Kantar Health, New York, NY, USA; 2Global Health Economics and Outcomes Research, Pfizer, Inc., New York, NY, USA; 3Global Health Economics and Outcomes Research, Pfizer, Inc., Groton, CT, USA; 4Global Research and Development, Pfizer, Inc., Groton, CT, USABackground: Several studies have documented a significant association between vasomotor symptoms (VMS) and a decrement in health outcomes among postmenopausal women, but these studies have mostly focused on the US. The aim of the current study was to broaden this investigation by examining the burden of VMS symptoms in the European Union with respect to both humanistic and economic outcomes.Methods: All women aged 40–75 years who completed the 2010 5EU (France, Germany, Italy, Spain, and the UK) National Health and Wellness Survey were identified as potential respondents and invited to participate in an additional cross-sectional, Internet-based survey. Only postmenopausal women from 5EU were included in the current analyses (n = 3801). VMS was assessed using the Menopausal Rating Scale, and was used in multiple regression models as the primary predictor of health status (EQ-5D-3L), work productivity loss, and the number of physician visits due to menopause.Results: Over half (50.3%) of postmenopausal women experienced either mild (24.6%), moderate (17.6%), or severe (8.1%) VMS. Controlling for confounding variables, mild (b = −0.03, P < 0.05), moderate (b = −0.07, P < 0.05), and severe VMS (b = −0.17, P < 0.05) were each associated with worse health utilities relative to women without VMS. Similarly, increased resource use (b = 1.04–2.39, all P < 0.05), overall work impairment (b = 8.71–19.69, all P < 0.05), and activity impairment (b = 11.22–24.54, all P < 0.05) were also observed as VMS severity increased (with each b representing the difference between each level of severity and the reference category).Conclusion: These results suggest a high prevalence of VMS in Western Europe. These symptoms are also associated with both humanistic and economic outcomes. Improved management of VMS may be able to increase the health status and ability to work productively as well as reduce societal direct costs.Keywords: menopause, vasomotor symptoms, health status, work productivity